Investigation of Spherical Roller Bearing and Deep Groove Ball Bearings with Various Defects Using Fft Analyser and Matlab Simulation - Ashish R. Pawar, Dattatray P. Kamble, Ganesh E. Kondhalkar, Kashinath H. Munde (Mathematical Statistician and Engineering Applications, 2020)
The bearing is very essential component in any mechanism. It is always running under high speed and high load conations. Failures in bearings often results in lengthy industrial downtime that has economic consequences. Prompt diagnostics of bearings failure is essential not only for the safe operation of machines, but also for the reduction of maintenance cost of any machine. Different methods are used for detection and diagnosis of defects of bearings; they may be broadly classified as vibration and acoustic measurements, temperature measurements and wear debris analysis. The most fundamental tool for bearing diagnosis is vibration analysis. The strength and weakness of vibration represents the location of defects. This paper discuss about the bearing failure diagnosis using vibration analysis. Crest factor is defined as the ratio of the peak value of a waveform to its RMS value. Comparative analysis is made between damaged and healthy Rolling and Ball bearings.FFT analyzer and accelerometer is use to perform experimental measurements in axial and radial directions